α-Linolenic acid induces apoptosis, inhibits the invasion and metastasis, and arrests cell cycle in human breast cancer cells by inhibiting fatty acid synthase - Wenyuan Huang (Journal of Functional Foods, 2022)
Fatty acid synthase (FASN) is an enzyme that synthesizes endogenous fatty acids. FASN overexpressed in various cancers, which indicates the involvement of FASN in cancer progression. α-Linolenic acid (ALA) is an omega-3 fatty acid with many biological activities, including anti-cancer effects. The aim of the present study was to investigate the inhibitory effect of ALA on fatty acid synthesis pathway and breast cancer cells apoptosis. We found FASN expression decreased significantly in ALA treated breast cancer cells. Compared with palmitic acid (PA), ALA reduced cell viability in a dose-dependent manner. ALA showed a higher affinity with the TE domain than PA. ALA induced breast cancer cells apoptosis, which effects were similar with the knockdown of FASN. In addition, ALA inhibited the invasion and metastasis, and arrested cell cycle in breast cancer cells. We propose a hypothesis that ALA could contribute to the treatment of human breast cancer by inhibiting FASN.